2015
DOI: 10.1128/mcb.00562-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Fenofibrate-Induced Metabolic Catastrophe and Glioblastoma Cell Death

Abstract: e Fenofibrate (FF) is a common lipid-lowering drug and a potent agonist of the peroxisome proliferator-activated receptor alpha (PPAR␣). FF and several other agonists of PPAR␣ have interesting anticancer properties, and our recent studies demonstrate that FF is very effective against tumor cells of neuroectodermal origin. In spite of these promising anticancer effects, the molecular mechanism(s) of FF-induced tumor cell toxicity remains to be elucidated. Here we report a novel PPAR␣-independent mechanism expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
90
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 60 publications
6
90
1
Order By: Relevance
“…This attention prompts us to investigate whether the protective effect of fenofibrate in cisplatin-induced toxicity in renal proximal tubular cells, alters the anticancer effect of cisplatin. Interestingly, fenofibrate alone reduced cell viability of tested cancer cells including colon, lung, and liver, correlating well with a recent study showing fenofibrate has antitumor activity (Wilk et al, 2015). In addition, fenofibrate did not alter the anticancer activity of cisplatin.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This attention prompts us to investigate whether the protective effect of fenofibrate in cisplatin-induced toxicity in renal proximal tubular cells, alters the anticancer effect of cisplatin. Interestingly, fenofibrate alone reduced cell viability of tested cancer cells including colon, lung, and liver, correlating well with a recent study showing fenofibrate has antitumor activity (Wilk et al, 2015). In addition, fenofibrate did not alter the anticancer activity of cisplatin.…”
Section: Discussionsupporting
confidence: 67%
“…Potentially, cytotoxicity following high concentration cisplatin exposure was attenuated by fenofibrate but no other fibrates. As fenofibrate acts via a PPARα-independent mechanism (Asavapanumas et al, 2012;Wilk et al, 2015), checking whether the renoprotective effect of fenofibrate is mediated by PPARα activation was essential. Employing PPARα inhibition via a PPARα antagonist, GW6471, fenofibrate's protective effect was maintained, suggesting PPARα activation is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate has anti-glioma effects also via PPARalpha agonism [111][112][113][114] and by related adenosine triphosphate (ATP) depletion in glioma cells. 113 Empirical evidence indicated a fenofibrate-mediated decrease in stemness mediators CD133 and transcription factor Oct4 in glioma cell populations.…”
Section: Fenofibratementioning
confidence: 99%
“…113 Empirical evidence indicated a fenofibrate-mediated decrease in stemness mediators CD133 and transcription factor Oct4 in glioma cell populations. 114 A seven-drug cocktail to treat a G-CSF producing tumor-progressive medulloblastoma using fibrate is in current clinical trial in Austria (ClinicalTrials.gov Identifier: NCT01356290, the MEMMAT regimen).…”
Section: Fenofibratementioning
confidence: 99%
“…Wilk et al 157 found that FF accumulated in mitochondria instead of the active form of the drug, the fenofibric acid, so that unchanged FF was the responsible of the activity on this organelle. This finding shows that FF and fenofibric acid may exhibit different pharmacologic activities (Figure 8), and explains the efforts done to find a suitable carrier to FF that would permit the arrival of this pharmaceutical to the tumor before being cleaved to FA 174 .…”
mentioning
confidence: 99%